Insights in the Structural Hierarchy of Statically Crystallized Palm Oil - Fien De Witte; Ivana A. Penagos; Kato Rondou; Kim Moens; Benny Lewille; Daylan A. Tzompa-Sosa; Davy Van de Walle; Filip Van Bockstaele; Andre G. Skirtach; Koen Dewettinck (Crystals, 2024)
Palm oil (PO) is still widely used for the production of all types of food products. Due to its triacylglycerol (TG) composition, PO is semisolid at ambient temperature, offering possibilities for many applications. In order to tailor the fat crystal network for certain applications, it remains imperative to understand the structural build-up of the fat crystal network at the full-length scale and to understand the effect of processing conditions. In this study, PO was crystallized under four temperature protocols (fast (FC) or slow (SC) cooling to 20 °C or 25 °C) and was followed for one hour of isothermal time. A broad toolbox was used to fundamentally unravel the structural build-up of the fat crystal network at different length scales. Wide-angle and small-angle X-ray scattering (WAXS and SAXS) showed transitions from α-2L to β’-2L over time. Despite the presence of the same polymorphic form (β’), chain length structure (2L), and domain size, ultra-small-angle X-ray scattering (USAXS) showed clear differences in the mesoscale. For all samples, the lamellar organization was confirmed. Both cooling speed and isothermal temperature were found to affect the size of the crystal nanoplatelets (CNPs), where the highest cooling speed and lowest isothermal temperature (FC and 20 °C) created the smallest CNPs. The microstructure was visualized with polarized light microscopy (PLM) and cryo-scanning electron microscopy (cryo-SEM), showing clear differences in crystallite size, clustering, and network morphology. Raman spectroscopy was applied to confirm differences in triglyceride distribution in the fat crystal network. This study shows that both cooling rate and isothermal temperature affect the fat crystal network formed, especially at the meso- and microscale.